Field study on the effect of vegetation on the performance of soil methanotrophy-based engineered systems – Column experiments. (April 2022) - Attalage, Dinu S.; Hettiaratchi, Patrick A.; Jayasinghe, Poornima; Dunfield, Peter F.; Smirnova, Angela V.; Rathnavibushana, Upeksha K.; Erkmen, Melissa; Kumar, Sunil
Abstract: Current literature provides conflicting information on the role vegetation plays when considering methane (CH4 ) oxidation potential of engineered Biosystems, such as landfill biocovers (LBCs), bio-windows and methane biofilters. The primary objective of this study was to determine whether the impact of vegetation on biological CH4 oxidation was positive or negative and to explain the reasons for the observations using a variety of experiments. A total of eight flow-through columns (two alfalfa, two native grass, two canola and two bare-soil replicates) were set up outdoors to simulate field operation in cold climatic conditions. Each column was layered with 18 cm of topsoil and 32 cm of compost mixture (compost 30%: topsoil 70% v/v) as packing material and treated with CH4 fluxes ranging from 180 to 815 g CH4 m −2 d −1 . The bare-soil columns exhibited the highest CH4 oxidation rate of 455 g CH4 m −2 d −1, while the maximum CH4 oxidation rates for the vegetated columns ranged between 147 and 171 g CH4 m −2 d −1 with the alfalfa column showing the lowest. Gas profiles of vegetated columns showed high concentrations of nitrogen (N2 ) and oxygen (O2 ) at all depths, possibly due to increased permeability created by the plant root systems. Quantitative Polymerase Chain Reaction (q-PCR) assessment showed that pmoA gene copy numbers, indicative of methanotrophic population levels, were higher in bare-soil columns than in vegetated columns. The Illumina based sequencing of 16S rRNA gene showed that Type I methanotrophs dominated both vegetated and bare-soil columns. Soil incubation experiments conducted to determine oxidation kinetic parameters also indicated greater methanotrophic activity in the bare-soil columns than in vegetated columns. The plant data collected at the end of the column experiments provided clear evidence of CH4 escape due to preferential pathways created by plant roots (reaching 38 cm, 31.5 cm and 26.5 cm by alfalfa, canola and native grass, respectively) that resulted in decreased CH4 oxidation in vegetated columns. The study results clearly demonstrate that vegetation decreases CH4 oxidation at high loading rates, notwithstanding the type of vegetation. Highlights: 16S rRNA sequencing showed γ-proteobacteria in vegetated and bare-soil column. The study validates that vegetation decreases CH4 oxidation at high loading rates. CH4 oxidation rate of 147–171 g CH4 m −2 d −1 observed in vegetated soil columns.